Lithic materials in high fluvial terraces of the central Pyrenean piedmont (Ebro Basin, Spain). (30th January 2016) - Montes, Lourdes; Domingo, Rafael; Peña-Monné, José Luis; Sampietro-Vattuone, María Marta; Rodríguez-Ochoa, Rafael; Utrilla, Pilar
Abstract: Lithic materials from Lower Palaeolithic are scarce in the Ebro Basin. Archaeological surveys carried out in some alluvial terraces on central Pyrenean piedmont have unearthed three new sites with remains of lithic industries related to cobble and core technology and large cutting tools. In the upper terrace levels (T1 and T2) from the Alcanadre and Cinca rivers, some pieces have been recovered on the surfaces: cobble-tools at Las Fitas and bifacial tools at San Quílez. The approximate age of these levels ranges between 780 ka and 1000 ka, established by paleomagnetism and evolutionary stages of calcrete. A cleaver was interbedded into a terrace (T5 level) of a minor tributary of the Cinca River (Olriols), whose age has been established at a regional scale between 178/151 ka. This T5 level is related to one of the cold phases of greater advance of Pyrenean glaciers during MIS 6. These new findings help us to widen our knowledge of a poorly known period of the human occupation of the middle Iberian basin. The chronological imprecision of most of the lithic materials has been partially overcome by means of geomorphological data, which offers a generic chrono-cultural framework for the people who used them.